Structural study of mono- and binuclear 2,6-Diacetylpyridine bis(nicotinoylhydrazone) coordination compounds - Danilescu, Olga (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2018)
2,6-Diacetylpyridine bis(nicotinoylhydrazone) (H2L) represents a Schiff base condensation product of 2,6-diacetylpyridine and nicotinic acid hydrazide and may represent a versatile ligand for a variety of research objectives because it has multiple coordination sites. In this review, the design of seven coordination compounds of the title ligand H2L with some transition metals-V(II, IV), Fe(III), and Co(II)-is reported. The V(IV), Fe(III), and Co(II) metals give rise to the mononuclear compounds where the metal cations form pentagonal bipyramids, while V(II) forms a binuclear compound with the metal in a tetragonal pyramid environment. The characteristic IR oscillations of H2L in all complexes and promising adsorption properties are analyzed.